Effects of expansionary monetary policy on the agricultural commodities market - Aguiar Henrique Filho, Eduardo; Čermáková, Klára; Slaný, Martin, 1982-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2021)
Agricultural Commodities experienced a rise in prices during the first decade of the 2000s. Literature shows that monetary policies adopted by developed Economies can influence practically all economic indicators of Developing markets. This thesis aims to evaluate if certain variables of monetary policy can influence the price formation of three selected commodities: soy, corn and sugar. Secondly, the study analyzes the price formation of these commodities during a period of expansionary monetary policy to better understand how they are influenced by unconventional instruments. The central hypothesis is that an excessive liquidity created by the FED spills over to Emerging Economies, boosting investment and consumption there and, lastly, causing a commodity cycle. In the theoretical part, this study brings an overview of global liquidity and its transmission mechanisms, spillovers and its transmission mechanisms and how commodities can be impacted by monetary policy, using different approaches. In the practical part two models are developed to test this hypothesis, and the results show that monetary policy does affect commodity prices and that each commodity responds differently for each variable used. The fact that people have more capital due to credit obtained from loans seems to influence the price of Sugar; Soy is highly influenced by exchange rates of Emerging markets and Corn is not very responsive to the used variables, that might be due to the high production of this commodity in the U.S. and the protectionist policies adopted by the government. This thesis could conclude that an expansionary monetary policy is capable of impacting agricultural commodities’ prices, but by different channels due to specificities of each commodity.
Vedoucí práce: Klára Čermáková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses